Analysis of the remote laser cutting process induced damage in carbon fibre reinforced polymers with cutting process simulations. Issue 1 (25th January 2021) - Schmidt, Benjamin; Rose, Michael; Zimmermann, Martina; Kästner, Markus
Abstract: Remote laser cutting in carbon fibre reinforced polymers is a promising machining technology, which can reduce the main drawback in laser cutting, the heat affected zone. As the heat affected zone has a strong influence on the mechanical behaviour of the composite, an exact characterisation is a key challenge for the simulation and design of fibre reinforced polymers. In order to reach this goal, a laser cutting process model is introduced. Based on the finite difference method, the heat transport is modelled on a macroscopic scale. The macroscopic material parameters are calculated with a rule of mixture. Matrix and fibre evaporation, which cause the formation of the matrix evaporation zone and the gap, are modelled with phase transitions and an adaption in the rule of mixture. The simulation results are validated with micro‐sections of the cutting gap.